PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY, TOTAL ASSET TURNOVER, DIVIDEN PAYOUT RATIO TERHADAP RETURN SAHAM PADA PERUSAHAAN OTOMOTIF - MATIUS WAHYUDI; TITA DEITIANA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this research is to test and analyze empirically the influence of current ratio, debt to equity ratio, return on equity, total asset turnover, and dividen payout ratio toward stock return. The object of this research is automotive sector companies that listed in Indonesia Stock Exchange period 2009-2015. The purposive sampling is used as sampling technique, where 8 companies met the criteria and were analyzed using Eviews9 panel data regression with fixed effect model to test the hyphotesis. The result of this research shows that current ratio, return on equity, total asset turnover influence stock return, while debt to equity ratio, and dividen payout ratio do not influence stock return.